A Balanced Proinflammatory and Regulatory Cytokine Signature in Young African Children Is Associated With Lower Risk of Clinical Malaria. (31st October 2018) - Dobaño, Carlota; Nhabomba, Augusto J; Manaca, Maria N; Berthoud, Tamara; Aguilar, Ruth; Quintó, Llorenç; Barbosa, Arnoldo; Rodríguez, Mauricio H; Jiménez, Alfons; Groves, Penny L; Santano, Rebeca; Bassat, Quique; et al.
Abstract: Background: The effect of timing of exposure to first Plasmodium falciparum infections during early childhood on the induction of innate and adaptive cytokine responses and their contribution to the development of clinical malaria immunity is not well established. Methods: As part of a double-blind, randomized, placebo-controlled trial in Mozambique using monthly chemoprophylaxis with sulfadoxine-pyrimethamine plus artesunate to selectively control timing of malaria exposure during infancy, peripheral blood mononuclear cells collected from participants at age 2.5, 5.5, 10.5, 15, and 24 months were stimulated ex vivo with parasite schizont and erythrocyte lysates. Cytokine messenger RNA expressed in cell pellets and proteins secreted in supernatants were quantified by reverse-transcription quantitative polymerase chain reaction and multiplex flow cytometry, respectively. Children were followed up for clinical malaria from birth until 4 years of age. Results: Higher proinflammatory (interleukin [IL] 1, IL-6, tumor necrosis factor) and regulatory (IL-10) cytokine concentrations during the second year of life were associated with reduced incidence of clinical malaria up to 4 years of age, adjusting by chemoprophylaxis and prior malaria exposure. Significantly lower concentrations of antigen-specific T-helper 1 (IL-2, IL-12, interferon-γ) and T-helper 2 (IL-4, IL-5) cytokines by 2 years of age were measured in children undergoing chemoprophylaxis compared to children receiving placebo ( P < .03). Conclusions: Selective chemoprophylaxis altering early natural exposure to malaria blood stage antigens during infancy had a significant effect on T-helper lymphocyte cytokine production >1 year later. Importantly, a balanced proinflammatory and anti-inflammatory cytokine signature, probably by innate cells, around age 2 years was associated with protective clinical immunity during childhood. Clinical Trials Registration: NCT00231452. Abstract : Prevention of exposure to Plasmodium falciparum infection during infancy significantly impacted antigen-specific T-helper 1 and 2 cytokine responses at age 2 years, and protection from clinical malaria was associated with balanced proinflammatory and regulatory cytokine/chemokine signatures characteristic of innate immune cells.